Contrasting Controls of Acidification Metrics Across Environmental Gradients in the North Pacific and the Adjunct Arctic Ocean: Insight From a Transregional Study. Issue 19 (5th October 2021) - Wu, Yingxu; Qi, Di; Ouyang, Zhangxian; Cao, Lu; Feely, Richard A.; Lin, Hongmei; Cai, Wei‐Jun; Chen, Liqi
Abstract: The spatiotemporal variabilities and drivers of ocean acidification (OA) metrics, [H + ], pH, and aragonite saturation state (Ωarag ) across environmental gradients remain poorly constrained. We use a novel high‐precision measurement of underway pH to investigate the hemispheric‐scale distributions of OA metrics from East Asia to the Arctic Ocean. While temperature and its induced air‐sea gas exchange fundamentally control the OA metrics distributions, we show that biological activity exerts the most prominent but different modifications on pH and Ωarag patterns. Strong photosynthesis counteracts the temperature‐driven pH pattern but reinforces that of Ωarag . Ice melt‐induced dilution in the Arctic Ocean additionally strengthens the Ωarag ‐temperature relationship but insignificantly affects [H + ] and pH. This study provides the first coherent assessment of comprehensive processes on OA metrics across large spatial regions, and highlights the potential of sea‐ice melt in changing Ωarag distribution, which should be included by Earth system models projecting future climate change. Plain Language Summary: The ocean uptake of anthropogenic carbon dioxide (CO2 ) is causing increase in hydrogen ion concentration ([H + ]) and reductions in pH and carbonate mineral aragonite saturation state (Ωarag ), together of which are commonly referred to as ocean acidification (OA). The coupled behavior of these affected OA metrics responding to physical and biogeochemical processes across environmental gradients has barely been examined in a comparative manner. To address this issue, we conduct a survey measuring high‐precision underway pH from East Asia to the Arctic Ocean. We find that, besides the temperature effects, which ultimately control the distributions of OA metrics, biological activity induces the strongest interruptions. Photosynthesis weakens the temperature‐driven pH pattern but reinforces that of Ωarag . In addition, ice melt‐induced dilution in the polar region strengthens Ωarag ‐temperature relationship but makes less difference to [H + ] and pH. These findings are important as they are based on the first large‐scale direct measurements of underway pH, and have implications for future studies on ocean acidification in the context of climate change. Key Points: High‐frequency underway pH across large spatial regions is measured, which is very rare in the oceanographic community Biological activity counteracts temperature‐driven pattern in pH, but reinforces that in Ωarag Sea‐ice melt driven dilution in the polar regions contributes significantly to lowering Ωarag